IMPLEMENTING CONTEXT-BASED AND CREATIVITY-BASED MATERIALS TO IMPROVE SCIENCE LITERACY OF ELEMENTARY SCHOOL STUDENTS - Sri Mulyani; Santoso Santoso; Ahmad Hilal Madjdi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This study aimed to describe the implementation of context-based and creativity-based materials at grade V SD Negeri Pangkalan in order to support the development of materials to increase students’ learning outcome. This research was development research consisting of ten steps. The needs analysis was conducted based on teachers’ and students’ perceptions carried out on 21 students at the 5th grade as the experimental class and 20 students in the control class. The data were collected through a questionnaire and a test of students’ learning outcomes. The needs analysis consisted of four aspects: content, linguistics, presentation, and graphic. This study revealed that 80.9% students who were taught through Context-based and Creativity-based materials achieved the learning completeness. Meanwhile, in the control class, only 60% student achieved the learning completeness. Thus, Context-based and Creativity-based materials were effective to improve the students’ scientific literacy.